LONG-TERM OUTCOMES IN MEDICALLY TREATED MOYAMOYA DISEASE. Issue 12 (15th November 2016) - Zarkali, Angeliki; Brown, Nicholas; Harding, Nicola; Grieve, Joan; Adams, Matthew; Ganesan, Vijeya; Simister, Robert; Brown, Martin
Abstract : Objectives: Moyamoya disease is a rare progressive intracranial vasculopathy, leading to recurrent cerebrovascular events. Revascularisation surgery is advocated as the treatment of choice despite little evidence supporting benefit over conservative management. We reviewed the outcome of patients attending an adult moyamoya clinic in our tertiary centre to determine the value of conservative treatment. Methods: We prospectively included all patients referred to the clinic from 2003 until June 2015. Conservative management included stopping antiplatelets, maintaining blood pressure below 135/90, statin therapy and lifestyle advice. Patients had repeat imaging and clinical assessments every 2 years. Results: 101 patients were followed up for an average of 8.4 years (range 0 to 28). 58 patients (57.4%) were managed conservatively, while 43 (42.6%) also received revascularisation surgery. We found no significant difference between surgically and conservatively treated patients in the occurrence of headache (p=0.839) and focal neurological symptoms (p=1.000) on last appointment or radiological disease progression (p=1.000). Smoking was the only factor associated with long-term focal symptoms (OR=4.04, 95% CI [1.03–16.52], p=0.036) or radiological progression (OR=4.61, 95% CI [1.21–18.29], p=0.012). Conclusion: Aggressively managing vascular risk factors and particularly smoking cessation is vital in adult moyamoya disease. Selection for revascularisation should be strict and carefully considered.